2006
DOI: 10.1002/app.22428
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification on nanoscale titanium dioxide by radiation: Preparation and characterization

Abstract: Electron beam mutual radiation to induce graft polymerization has been carried out respectively, between nanoscale anatase‐ or rutile‐titanium dioxide particles surface and methyl methacrylate (MMA). The composition and properties of surface modified titanium dioxide were investigated by a number of surface sensitive techniques: X‐ray photoelectron spectrum (XPS), FTIR, X‐ray diffraction (XRD), and NMR. Results of the technological measurements show how surface chemistry is affected throughout the surface modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Among the developments in nanotechnology, the encapsulation of inorganic nanoparticles, such as silica , calcium carbonate , antimony trioxide , halloysite , alumina , zinc oxide , ferric oxide , and titanium dioxide (TiO 2 ) , by polymers, such as polystyrene , poly(2‐hydroxyethyl methacrylate) , poly(methyl methacrylate) (PMMA) , and poly(butyl methacrylate)‐ block ‐poly(methyl methacrylate) , has been the object of intensive research in the field of materials science and has received interest in a wide range of industrial fields. Although inorganic materials exhibit a high rigidity, thermal resistance, and mechanical strength , polymers exhibit a higher degree of flexibility, toughness, and processability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the developments in nanotechnology, the encapsulation of inorganic nanoparticles, such as silica , calcium carbonate , antimony trioxide , halloysite , alumina , zinc oxide , ferric oxide , and titanium dioxide (TiO 2 ) , by polymers, such as polystyrene , poly(2‐hydroxyethyl methacrylate) , poly(methyl methacrylate) (PMMA) , and poly(butyl methacrylate)‐ block ‐poly(methyl methacrylate) , has been the object of intensive research in the field of materials science and has received interest in a wide range of industrial fields. Although inorganic materials exhibit a high rigidity, thermal resistance, and mechanical strength , polymers exhibit a higher degree of flexibility, toughness, and processability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hybrid nanoparticles are often designed for use as reinforcement to prepare high‐performance polymer nanocomposites with a substantial improvement in the overall performance compared with the neat polymers or conventional composites, even at a very small addition of the nanoparticles. Among inorganic nanoparticles, TiO 2 has been extensively used for photocatalysts, solar cells, paints, protective coatings, optical fibers, and polymer nanocomposites because of its unique properties, such as physicochemical stability, photostability, self cleaning, nontoxicity, and resistance to discoloration under ultraviolet light . Wang et al introduced aminopropyl trimethoxy silane‐grafted nanosized titanium dioxide (nTiO 2 ) into poly(ε‐caprolactone) to prepare (poly[ε‐caprolactone])/TiO 2 nanocomposites by in situ polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have improved the stability of TiO 2 particles by modification. The feasibility of using organic functional groups to produce chemical bonds on the particle surface was verified. Xerox used a thermoplastic resin that hardened after it had precipitated on the pigment to improve the chemical stability . A silane coupling agent and a titanate coupling agent were used for modification of inorganic particulates. , Some researchers had reported that surface modification with silane coupling agents provided a thin layer on the inorganic oxide surface. , However, the modification of inorganic oxide particles was usually carried out in an organic solvent, which created environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, nTiO 2 particles contain a large amount of hydroxyl groups (-OH) on the surface, which cause a strong filler-filler interaction through hydrogen bindings, a high tendency for agglomeration and an uneven dispersion in the polymer matrix during processing, and so the anticipated improvement in mechanical and thermal properties of the nanocomposites may not be found. To solve these problems, a number of the academic researchers have focused on grafting the appropriate polymers onto the inorganic nanoparticle surfaces in order to prevent their self-agglomeration and thus significantly enhance the nanoparticle stability and dispersion within the polymer matrix, which allow better stress transfer from HIPS matrix to the hybrid nanoparticles, resulting in an increase in the thermal and mechanical properties [15,[20][21][22][23][24][25][26]. In this work, PS molecules were grafted onto nTiO 2 particles via in situ differential microemulsion polymerisation, which was regarded as an effective process for encapsulating inorganic nanoparticles [20,21,23,24].…”
Section: Introductionmentioning
confidence: 99%